Antitrust Analysis of Online Sales Platforms & Copyright Limitations and Exceptions (LIDC Contributions on Antitrust Law, Intellectual Property and Unfair Competition,, 2018)
This book gathers international and national reports from across the globe on key questions in the field of antitrust and intellectual property. The first part discusses the application of competition law to online sales platforms, which is increasingly a focus for anti-trust authorities around the world. A detailed international report explores which are the major challenges for competition law generated by the growth of online platforms. It provides an excellent comparative study of this complex and challenging subject. The second part of the book gathers contributions from various jurisdictions on the topic "To what extent do current exclusions and limitations to copyright strike a fair balance between the rights of owners and fair use by private individuals and others ?" This section presents an international report, which offers an unparalleled comparative analysis of this topic, bringing together common themes and contrasting the various national provisions dealing with exceptions to copyright, amongst other things. The book also includes the resolutions passed by the General Assembly of the International League of Competition Law (LIDC) following a debate on each of these topics, which include proposed solutions and recommendations. The LIDC is a long-standing international association that focuses on the interface between competition law and intellectual property law, including unfair competition issues.